Evaluating ṣukūk investment intentions in Pakistan from a social cognitive perspective - Safeer Ullah Khan; Ikram Ullah Khan; Ismail Khan; Saif-ud-Din Khan; Abid Ullah Khan (ISRA International Journal of Islamic Finance, 2020)
Purpose: This study aims to evaluate cognitive, personal and environmental factors affecting investors' behavioral intentions (BI) to invest in ṣukūk (Islamic investment certificates) in Pakistan. Design/methodology/approach Data from 462 participants were collected through survey-questionnaires by using the convenient sampling technique. Hypothesized proposed relationships among the constructs were examined by applying the structural equation modeling (SEM) technique through smart partial least squares. Findings Compatibility, internal influence, external influence and intrinsic motivation were found to be significant predictors of investors' BI to invest in ṣukūk. In addition, it was found that the religious aspect not only affects investors' BI positively but also works as a moderator in the relationships between BI and both internal and external influence. Practical implications The results are quite helpful for ṣukūk issuers and regulators to consider cognitive, personal and environmental factors that might enhance the adoption of ṣukūk, especially among Muslim investors. Originality/value This study is among the few research studies that shed light on investors' BI to invest in ṣukūk. Using social cognitive theory, the study investigates the cognitive, personal and environmental factors influencing ṣukūk adoption, which were previously unexplored. In addition, this is the first study that unveils the influential factors of ṣukūk adoption in Pakistan, a Muslim-majority country.
Keywords: 330